Field effects of oxygenated monoterpenes and estragole combined with pheromone on attraction of Ips typographus and its natural enemies - Moliterno, Antonioni Acacio Campos; Jakuš, Rastislav; Modlinger, Roman; Unelius, C. Rikard; Schlyter, Fredrik; Jirošová, Anna (Frontiers in Forests and Global Change, 2023)
Introduction Central European Norway spruce monocultures face Ips typographus outbreaks due to decreasing resistance. These beetles use volatile compounds to communicate and select suitable host trees. Spruce trees, beetles, and their symbiotic ophiostomatoid fungi emit oxygenated monoterpenes, including 1,8-cineole, α-terpineol, camphor, carvone, terpinen-4-ol, isopinocamphone, and pinocamphone, and the phenylpropanoid estragole, particularly in the infestation phase. These compounds trigger strong responses in I. typographus antennae, motivating our field study. Objective This study aimed to assess how adding these compounds to the aggregation pheromone of Ips typographus modulates the attraction of this bark beetle and its natural enemies. Methods In combination with I. typographus pheromone, estragole, 1,8-cineole, (±)-camphor, (–)-carvone, alpha-terpineol, (–)-terpinen-4-ol, (+)-pinocamphone, and (+)-isopinocamphone at low, medium, and high doses were tested in pheromone traps at two sites in the Czech Republic. Results All 1,8-cineole doses and the high estragole dose acted as anti-attractants for I. typographus, whereas all (+)-isopinocamphone doses enhanced their attraction to pheromone. Catches of natural enemies, the Staphylinidae and Pteromalidae, varied by location. Conclusion 1,8-cineole, isopinocamphone, and estragole may play vital roles in tritrophic interactions among spruce trees, and I. typographus and its natural enemies, and these compounds may be developed into new or enhanced semiochemical-based pest control methods.